2008
DOI: 10.1002/mpr.254
|View full text |Cite
|
Sign up to set email alerts
|

What are the high risk periods for incident substance use and transitions to abuse and dependence? Implications for early intervention and prevention

Abstract: Except for alcohol the time windows for targeted intervention to prevent progression to malignant patterns in adolescence are critically small, leaving little time for targeted intervention to prevent transition. The fast transitions to abuse and dependence in adolescence may be indicative for the increased vulnerability to substance effects in this time period. Basic research on the determinants of transitions should thus target this period in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 38 publications
4
101
0
6
Order By: Relevance
“…Sensitivity to reward has been shown to be associated with a stronger physiological response to alcohol intake as well as an increase in conditioned responses to alcohol cues (Brunelle et al, 2004). In addition, early initiation of alcohol intake was found to be associated with an elevated risk for the development of alcohol use disorder (Behrendt et al, 2009), specifically in adolescence, since this period was characterized as a high risk period for first alcohol use and the transition to alcohol abuse and dependence (Wittchen et al, 2008;Swendsen et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity to reward has been shown to be associated with a stronger physiological response to alcohol intake as well as an increase in conditioned responses to alcohol cues (Brunelle et al, 2004). In addition, early initiation of alcohol intake was found to be associated with an elevated risk for the development of alcohol use disorder (Behrendt et al, 2009), specifically in adolescence, since this period was characterized as a high risk period for first alcohol use and the transition to alcohol abuse and dependence (Wittchen et al, 2008;Swendsen et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Early initiation of alcohol intake, even at very low levels of alcohol use, was found to be associated with an elevated risk for the development of alcohol use disorder (Behrendt et al, 2009). Specifically, adolescence was characterized as a high risk period for first alcohol use and the transition to alcohol abuse and dependence (Wittchen et al, 2008;Swendsen et al, 2009). Neurobiological factors such as deficient recruitment of motivational circuitry by non-drug rewards (Ratsma et al, 2002) and psychosocial factors such as adverse life events resulting from deviant and risky behavior (eg, Clark et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Model IIA : as model II but with additional adjustment for anxiety disorders that predicted the respective alcohol use disorder (AUD) in model II and for an aggregated variable including generalized anxiety disorder, obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), agoraphobia without history of panic disorder and panic disorder. gender differences in the speed of transition to AD (Wagner & Anthony, 2007 ;Wittchen et al 2008). Nicotine dependence and cannabis use disorders were not associated with more rapid transitions to AUD, possibly because their main incidence phases overlap with those of AUD (Wittchen et al 2008).…”
Section: Earlier Pmd Onsetmentioning
confidence: 95%
“…Female gender has been linked with faster transitions to alcohol problems (Randall et al 1999), but more recent studies found no or little evidence for a faster AUD development in women (Wagner & Anthony, 2007 ;Wittchen et al 2008). We hypothesized that there are no gender differences in the speed of transition to AUD.…”
Section: Introductionmentioning
confidence: 91%
“…In order to prevent (party-)drug use or reduce its harmful effects, interventions are often targeted at young adults, most notably vocational, college, and university students, as drug initiation and regular use peak around young adulthood (Arria et al, 2008;Arria, Vincent, & Caldeira, 2009;Dennhardt & Murphy, 2013;Wittchen et al, 2008). However, descriptions of party-drug use among students, including the use of trending partydrugs such as NPS, are lacking.…”
Section: Introductionmentioning
confidence: 99%